ZnO1−xSx Nanosphere in Ferroelectric Liquid Crystal Matrix: The Effect of Aggregation and Defects on the Dielectric and Electro-Optical Properties - Dharmendra Pratap Singh; Swadesh Kumar Gupta; Rajiv Manohar (Advances in Condensed Matter Physics)
High concentration (5 wt %) of ZnO1−xSx nanosphere (NS) has been dispersed in the ferroelectric liquid crystal (FLC) to analyze the effect of high dopant concentration in the FLC matrix. The FLC molecules actively interact with the NS. The presence of NS enhances the photoluminescence of the pure FLC material due to the coupling of localized surface plasmon resonance from NS with FLC molecules. The high concentration of NS causes an aggregation in the FLC matrix and creates topological defects. The defects and aggregation cause the change in electro-optical and dielectric properties of the pure FLC material. The bigger size of NS as compared to the smectic layer separation causes the warping in the smectic layer. Semiconducting nature of NS also affects the conductivity of the pure FLC.